Analisis penerapan Peraturan Pemerintah Nomor 55 dalam upaya meningkatkan kepatuhan wajib pajak UMKM di Kantor Pelayanan Pajak Pratama Bitung - Dalope, Chicilia Afrilin Chaya; Kalangi, Lintje; Latjandu, Lady Diana (Yayasan Widyantara Nawasena Raharja, 2025)
Government Regulation (PP) No. 55 of 2022 aims to simplify taxation for Micro, Small, and Medium Enterprises (MSMEs) by providing incentives such as tax exemptions for businesses with an annual turnover of less than IDR 500 million, and by implementing a final income tax (PPh) rate of 0.5% for MSMEs with a turnover of up to IDR 4.8 billion. While this policy has led to an increase in MSME taxpayer registrations, the level of tax reporting compliance remains low due to limited understanding and inadequate socialization. This study analyzes the implementation of PP No. 55 of 2022 at the Bitung Primary Tax Office (KPP Pratama Bitung), with the objective of evaluating its effectiveness and identifying the challenges in enhancing MSME tax compliance. A qualitative descriptive approach was employed, using interviews and documentation as data collection methods. The findings indicate that the regulation has been socialized by the tax office and has positively influenced taxpayer compliance, particularly in terms of registration and reporting. However, challenges persist, especially with respect to timely submission of annual tax returns (SPT). To improve compliance, further efforts are required in the form of intensified socialization and the provision of targeted mentoring programs for MSMEs.